Quality of life among elderly: the view from appetite and anthropometry characteristic perspective - Azam, Syafinas; Adznam, Siti Nur ‘Asyura; Chan, Yoke Mun; Ibrahim, Zuriati; Mohd Taib, Mohd Nasir; Hamzah, Nur Aqlili Riana (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The world’s population ageing is poised to growth in number including in Malaysia. In conjunction with the transition of the nation toward ageing population, the Quality of Life (QoL) among elderly should be maintain or improved to good level. This study was to investigate the relationship between appetite, anthropometric characteristic and QoL among elderly people in the Federal Land Development Authority (FELDA) Schemes, Johor, Malaysia. Methods: This cross-sectional study involved a total of 269 elderly (130 men and 139 women), with mean age of 69.50 ± 5.221. Elderly in FELDA Air Tawar 4, FELDA Air Tawar 5 and FELDA Bukit Batu were sampled using probability proportionate to size sampling. Data on age, monthly income and marital status were collected using questionnaire guided face-to-face Interviewed by trained researcher through house to house visit. Appetite was measured with Simplified Nutritional Appetite Questionnaire, height with stadiometer, weight with weighing scale, waist circumference with measuring tape and QoL with Short Form-36. The findings were analyzed using IBM SPSS statistics version 22 software. Results: The majority of subjects were classified as good appetite, obese and large waist circumference. Role limitations due to emotional problems domain was highest mean score of QoL, while physical functioning domain the lowest mean score of QoL. Appetite (r = 0.260; p < 0.001), body mass index (r= -0.136; p < 0.001) and waist circumference (r= -0.191; p = 0.002) were correlated with physical component summary of QoL. However, they were not correlated with mental health component summary of QoL. Conclusion: Most of the elderly are at good level of appetite, in obesity weight group, high risk of co-morbidities based on waist circumference measurement and at sensible level of QoL. Furthermore, as appetite, body mass index and waist circumference do have relation with physical component summary of QoL, thus, it is pivotal to include those factors as domain in planning health promotion program with aimed to increase QoL level among the elderly.